OPTIMALISASI PERAN KADER DALAM PENGEJAWANTAHAN GERMAS - Endang Sri Wahyuni; Roh Hastuti Prasetyaningsih (Jurnal Empathy Pengabdian Kepada Masyarakat, 2022)
Background: Malnutrition that causes stunting, which is a global problem today, requires very serious and comprehensive treatment. One of the efforts made by the government is to launch a Community Movement for Healthy Living (Gerakan Masyarakat Hidup Sehat "Germas") program through a cadre system to improve community empowerment programs. The purpose of this community service activity is to optimize the role of cadres in the Germas application. Methods: Using a total sampling technique (33 cadres), counseling methods using power points and leaflets. The evaluation was carried out by comparing the results of the pre-extension questionnaire (mean = 6.24; post-extension, mean = 7.45). Results: A different test was carried out using the Wilcoxon Signed Rank Test, the Z value was (-5.096b). Conclusion: There is an effect of providing counseling using power points and leaflets on the level of knowledge of cadres about optimizing the role of cadres in embodying Germas.